The Impact of Batik Sewage Disposal Towards The Quality of Dug-Well Water in The Batik Industry Center of Jenggot Pekalongan City - Slamet Budiyanto; Anies Anies; Hartuti Purnawerni; Henna Rya Sunoko (Journal of Public Health for Tropical and Coastal Region, 2019)
The development of batik industry in Indonesa today is quite rapid after batik has been acknowledged by UNESCO as the intangible world heritage from Indonesia. Pekalongan City is well-known as “Batik City” and it is one of the biggest batik industry centers in Indonesia with its 917 batik industries. Jenggot (administrative) village is one of the biggest batik industry centers in Pekalongan with 203 artisans of batik indstries. The process of batik making needs some dye of synthetic one containing heavy metals one of which is Pb. The present condition, most of the batik industry sewage in Jenggot goes straight to the environment without prior treatment. The purpose of this research is to find out the impact of the disposal of batik sewage containing heavy metal Pb towards the quality of dug-well water around the areas of batik sewage disposal.This is descriptive analytical research with cross-sectional approach method. The research was conducted by taking direct samples of sewage in the community of batik industries, i.e the sample that floods the residential drain and the sample of dug well around the sewage flood. The sample was tested in the laboratory with the AAS instrument.The result of this study, out of  67 samples of batik sewage, showed 17 samples (25.4%) contained heavy metal Pb above the quality standar set, i.e 0.03 mg/L. Twenty (20) samples (29.9%) out of 67 samples of water puddle in the residential areas was above the standard quality set, i.e 0.03 mg/L. As to the quality of dug well, it was found 129 samples (61.4%) out of 210 kinds of well water contained heavy metal Pb above standard quality set, i.e. 0.01 mg/L.This result showed that the quality of environment has declined marked by the polluted dug-well water of the inhabitants around the batik industry center in Jenggot Pekalongan.